2017
DOI: 10.1186/s12955-017-0675-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of physical and mental health in persons with morbid obesity attending a patient education course – a two-year follow-up study

Abstract: BackgroundPeople with morbid obesity (body mass index ≥40) may experience changes in their health after participating in a tailored patient education course. The aims of this study were to assess the changes in physical and mental health in persons with morbid obesity during the 2 years following an educational course and to explore possible socio-demographic, treatment, and personal predictors of physical and mental health outcomes.MethodsIn this prospective longitudinal cohort study, self-report questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…The GSE rating has been linked with various physical and mental health outcomes ( Lerdal et al., 2017 ; Nygaard et al., 2017 ). In view of the higher prevalence of both mental and physical health problems in the SA group in our study, it is not surprising that they reported lower self-efficacy and poorer QoL than the non-SA group.…”
Section: Discussionmentioning
confidence: 99%
“…The GSE rating has been linked with various physical and mental health outcomes ( Lerdal et al., 2017 ; Nygaard et al., 2017 ). In view of the higher prevalence of both mental and physical health problems in the SA group in our study, it is not surprising that they reported lower self-efficacy and poorer QoL than the non-SA group.…”
Section: Discussionmentioning
confidence: 99%
“…The study carried out by Krukowski supports what we have been saying 26 , that, over time, the bond between professionals and participants favors the loss of weight of the patients. Other studies also show positive results of educational processes in preparing for bariatric operations, whether they are for long 27 or for short periods 28 . They provide tools that give the patients the strength to change behaviors.…”
Section: Changes In Posture Perceived By Patients In the Educational ...mentioning
confidence: 88%
“…Poucos autores 14,18,20,22,23 versam diretamente sobre atividades educativas em grupo, o que reafirma a justificativa do estudo de que sãonecessárias mais pesquisas sobre essa temática, pois poucas publicações abordam a importância de profissionais atuarem no tratamento a obesos grau III por meio de atividades de educação em saúde em grupo como uma ferramenta para auxiliar nesse cuidado.…”
Section: A Atenção Primária à Saúde E Atividades Em Grupo No Tratamenunclassified
“…Entretanto, a necessidade de tratamento especializado para esse público, com abordagem multidisciplinar, e a importância do apoio da rede familiar e dos profissionais são aspectos que aparecem no discurso de vários autores entre os selecionados [14][15][16][17][18]20,22,23,24 .…”
Section: A Atenção Primária à Saúde E Atividades Em Grupo No Tratamenunclassified